2017
DOI: 10.1002/2016jd025906
|View full text |Cite
|
Sign up to set email alerts
|

Tracking nitrous oxide emission processes at a suburban site with semicontinuous, in situ measurements of isotopic composition

Abstract: The isotopic composition of atmospheric nitrous oxide (N2O) was measured semicontinuously, at ∼35 min frequency in intermittent periods of 1–6 days over one and a half years, using preconcentration coupled to a quantum cascade laser spectrometer at the suburban site of Dübendorf, Switzerland. The achieved measurement repeatability was 0.08‰, 0.11‰, and 0.10‰ for δ18O, site preference, and δ15Nbulk respectively, which is better than or equal to standard flask sampling‐based isotope ratio mass spectrometry perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 116 publications
3
35
0
Order By: Relevance
“…Accordingly, average daytime N2O concentrations, δ 15 (Toyoda et al, 2013)). Observed changes in N2O concentrations and isotopic composition at night are within the range of previous studies from agricultural sites (Wolf et al, 2015;Toyoda et al, 2011), but clearly higher than variations measured at 13 m or 95 m above ground in an urban or suburban environment (Harris et al, 2014;Harris et al, 2017).…”
Section: Variability Of N2o Concentrations and Isotopic Composition Asupporting
confidence: 80%
See 3 more Smart Citations
“…Accordingly, average daytime N2O concentrations, δ 15 (Toyoda et al, 2013)). Observed changes in N2O concentrations and isotopic composition at night are within the range of previous studies from agricultural sites (Wolf et al, 2015;Toyoda et al, 2011), but clearly higher than variations measured at 13 m or 95 m above ground in an urban or suburban environment (Harris et al, 2014;Harris et al, 2017).…”
Section: Variability Of N2o Concentrations and Isotopic Composition Asupporting
confidence: 80%
“…Data processing was conducted as previously described by Harris et al (2017) using Matlab (MathWorks, Inc., USA). Abundances of the four isotopocules ( 14 N 14 N 16 O, 14 N 15 N 16 O, 15 N 14 N 16 O and 14 N 14 N 18 O) were obtained with TDL Wintel (Aerodyne Research Inc., Billerica, USA), and isotope ratios were drift-corrected for changes observed in S1.…”
Section: Calibration Strategy and Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The fractionation factors ε 18 O/ε 15 N bulk , ε 18 O/εSP, and ε 15 N bulk /εSP have been determined in a number of incubation experiments, and it has been suggested that their ratios (2.4, 2.8, and 1.2, respectively) may be indicators of N 2 O reduction (Koba et al, 2009). It has to be mentioned, however, that fractionation factors may deviate depending on environmental conditions (Koster et al, 2013) or even over the course of a single experiment due to multiple reaction steps involved (Haslun et al, 2018). Furthermore, δ 18 O-N 2 O of denitrification is affected by oxygen exchange between reaction intermediates (NO − 3 , NO − 2 ) and soil water as a function of WFPS (Well et al, 2008;Kool et al, 2011).…”
Section: Range Of N 2 O Source Signaturesmentioning
confidence: 99%